Шпионский роман как вариант детективного жанра в современном литературоведении - Норец, М.В. (Культура народов Причерноморья, 2013)
Данная работа посвящена анализу шпионского романа в контексте жанровой идентификации. Предпринята попытка дать определение шпионскому роману, выявить жанровую доминанту, рассмотреть жанровый код. Также автор уделяет внимание вопросам, касающимся истоков жанра, его эволюции в западном и постсоветском литературоведении, а также, принципиального отличия его от детектива. Дана робота присвячена аналізу шпигунського роману в контексті жанрової ідентифікації. Почата спроба дати визначення шпигунському роману, виявити жанрову домінанту, розглянути жанровий код. Також, автор приділяє увагу питанням, що стосуються джерел жанру, його еволюції в західному й пострадянському літературознавстві, а також, принципової відмінності його від детектива. This work is dedicated to the analysis of the spy novel in the context of genre identification. The author tries to give the definition to the spy novel, to find and define the dominant genre as well as analyze the genre code. Also the author pays attention to the questions, concerning the sources of the genre, its evolution in western and post-soviet literary criticism, and, also finds the principle difference between the spy novel and the detective. The author investigates the problem in the diachronic aspect. The springing up of the spy novel in Great Britain, its reasons and consequences at the end of the 19 – the beginning of the 20 century is analyzed by the author. The source of the spy novel dates back to the times of the Trojan horse. Also the emerging and development of the spy novel at the times of “cold war”, “thaw” is also under consideration. The author’s attention is paid to the development of the spy novel during the 20th century in the European countries, The USSR. The author considers the peak of the development of the spy novel to be the period of time after the second world war. The conditions of the bipolar world gave rise to different types of the spy novel.